1756 Can Children with Disabilities be Transported Safely? the Challenge and Solutions. (October 2012) - Bull, M; O'Neil, J; Talty, J; Yonkman, J; , MS; , OTR
Abstract : Background and Aims: Children with diverse medical problems are transported daily to school, medical appointments and family events. One-in-ten children worldwide have conditions that may require special consideration to ensure optimal transportation safety. How to safely transport this population is poorly understood. This initiative enhances understanding of correct occupant protection for children with disabilities. Method: Positioning problems and physiologic stability of children with developmental, skeletal, and physiologic abnormalities and behavioral concerns were reviewed and where needed special restraints were identified. Biomechanical principles were investigated and applied where possible. Solutions were sought for each condition involving a unique concern. A literature review was conducted and resources identified, many of which were developed by the authors. Results: Many infants and children with low birth weight or born prematurely, cerebral palsy, hypotonia, or spina bifida, and skeletal problems including children in casts following injury or surgery frequently cannot be safely transported in conventional car seats. Even within developed nations children with disabilities are suboptimally restrained. Solutions for difficult transportation problems have been developed and identified. Some problems remain unresolved and safety remains suboptimal for some conditions. Conclusions: Motor vehicle crashes are a leading cause of mortality and morbidity worldwide and children are often severely injured or killed. Appropriate use of child restraints has been shown to save lives and reduce injury. Solutions exist for many conditions and families benefit from assistance in identification and access to these solutions. Transportation options will be explained and care improved by the information in this presentation.